Exploring Sociocultural Constraints on Females’ Higher Education in Balochistan: A Mixed-Methods Study - Wahid, Shazia; Ali, Wazir; Baloch, Niamat Ullah (Universitas Negeri Semarang, 2025)
In Balochistan, females’ pursuit of higher education (HE) often encounters entrenched sociocultural constraints and economic barriers, despite Pakistan’s commitments to gender equality. The study aims to explore the intersecting challenges to female participation in HE in Balochistan through a convergent mixed-methods approach with survey data (289 participants) and seven semi-structured interviews conducted among female students. Quantitative results revealed persistent challenges: 46.5% of respondents reported unequal opportunities, and 78.3% financial hardship. Institutional obstacles were also widespread, including administrative bias (72.8%), gender discrimination (69.3%), and unequal access to activities (64.8%). Complementing these figures, qualitative findings highlighted resilience, with most participants articulating strong ambitions for educational and professional advancement, despite facing systemic and social challenges. Community attitudes were found to be uneven, as families with higher educational backgrounds expressed greater support for female higher education. The study concludes that addressing these challenges requires need-based scholarships, context-specific community engagement, and gender sensitive institutional reform. Further, policy recommendations to promote gender parity and foster an inclusive HE environment in rural Pakistan suggest that effective interventions must combine need-based scholarships, gender-sensitive reforms, and community engagement tailored to local contexts.